Pendugaan Parameter Genetik Populasi Cabai (Capsicum annuum L.) Melalui Pengujian F1 Hasil Persilangan Secara Diallel - Dedy alfian; Aslim Rasyad; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this research were to estimate genetic parameters such as variability, heritability, general combining ability (GCA), and specific combining ability (SCA),  of various agronomic traits in chili population through diallel cross. The research was arranged in a randomized complete block design in which 15 hybrids genotypes created by half diallel cross were evaluated with three replications. Seedlings of twenty eight days old was transplanted to a plot of 1 m x 5 m with planting space of 50 x 50 cm. Ten samples were chosen from each plot to obtain  plant height, height of stem dichotomous, weight per fruit, fruit length, fruit rind thickness, fruit diameter and fruit weight per plant. Data analyses were performed by analyses of variance and then translated to genetic parameters following the Griffing’s methods model IV. The results indicated that the value of GCA and SCA were significant for several characters but not for others. Due to its suitable GCA value, one genotype such as C5 may be selected as one parent to improve agronomic characters such as hastening days to flower and harvest,  increased stem diameter,  thick fruit pulp, fruit diameter, weight per fruit, and fruit weight per plant. Genotypes C120xC5 and C111xC19 may be utilized to improve stem diameter, thick fruit pulp, fruit diameter, weight per fruit, and fruit weight per plant. Heritability were significant for stem height,  dichotomous, stem diameter, fruit length, fruit flesh thickness, fruit diameter, total number of fruits per plant, and fruit weight per plant. Fruit rind thickness, fruit diameter, weight per fruit, and total number of fruits per plant was positively correlated to total fruit weight per plant.   Keywords  : Chili breeding, variability, heritability, combining ability